CONNEXIONS INTERLINGUISTIQUES REFLÉTÉES DE MANIÈRE LEXICOGRAPHIQUE. REGARD COMPARATIF : ROUMAIN, ITALIEN ET FRANÇAIS - MOROIANU, Cristian (Studia Universitatis Babeș-Bolyai Philologia, 2020)
Interlanguage Connections Reflected Lexicographically. A Comparative Study of Romanian, Italian and French. The present article focuses on the concept of etymological word family and the way in which it is reflected in three Romance languages – Romanian, Italian and French – by comparing the historical and cultural journey of one single Latin etymon. I have turned my attention to the Latin verb currere and its family, which have been inherited or borrowed in the three languages under discussion. Analysing the way in which these words are presented in the representative etymological and historical dictionaries (DELR for Romanian, DHLF for French and VLI for Italian), the productivity of the main etymon and its family and, implicitly, the underlying Latin model are discussed. The analysis emphasises both the situation from each individual language, and the inter-linguistic reality, making reference to the cultural contacts existing between the three languages and societies. Starting from an individual case, the main purpose of this study is to show the hereditary and cultural unity of Romanian, Italian and French and the way it has been reflected diachronically via linguistic means. REZUMAT. Conexiuni interlingvistice reflectate lexicografic. Privire comparativă: română, italiană și franceză. Studiul propus spre publicare urmărește configurarea și, mai ales, reflectarea conceptului de „familie lexico-etimologică” în trei dintre limbile romanice (româna, italiana și franceza), prin intermediul prezentării comparative a parcursului istoric și cultural al aceluiași etimon latin (moștenit). Pentru aceasta am ales, ca exemplu reprezentativ, verbul lat. currere (împreună cu componentele familiei sale interne), ale căror reflexe lexicale au fost moștenite sau împrumutate în cele trei limbi. Cu ajutorul unor dicționare istorice și etimologice considerate de noi reprezentative (DELR, pentru română, DHLF, pentru franceză și VLI, pentru italiană), am prezentat în paralel productivitatea etimonului și, implicit, a modelului structural latin pe care îl reprezintă, reflectată atât în mod independent, la nivelul fiecăreia dintre limbile discutate, cât și, mai ales, la nivel interlingvistic, prin contactele culturale manifestate între acestea. Scopul acestei cercetări este acela de a evidenția, plecând de la un exemplu particular, unitatea ereditară și culturală a limbilor română, italiană și franceză și modalitățile lingvistice prin care aceasta s-a configurat de-a lungul istoriei. Cuvinte-cheie: familie lingvistică, împrumut, moștenire, analogie, derivare.